Hepatitis C-related knowledge and attitude among adults on probation in a large US city - Matthew S. Minturn; Kevin F. Kamis; David L. Wyles; Tracy Scott; Hermione Hurley; Scott J. Prendergast; Sarah E. Rowan (BMC, 2024)
Abstract Background Hepatitis C virus (HCV) continues to cause significant morbidity and mortality within the US, and disproportionately impacts those involved with the criminal justice system. Despite this, knowledge and attitudes regarding HCV treatment among adults on probation have not been well studied. We conducted a cross-sectional survey of adults on probation accessing on-site HCV testing and linkage services at the adult probation department in Denver, Colorado. The survey assessed general knowledge of HCV and HCV treatment, as well as attitudes surrounding HCV treatment that might reflect medical mistrust. We used bivariate and multivariable logistic regression to identify factors associated with previous HCV testing, previous HCV treatment, and HCV antibody positivity at the time the survey was conducted. Results A total of 402 participants completed all or a portion of the survey. 69% of the participants were cis-gender men; 29% were white, 27% were Black, and 30% were Hispanic/Latinx. Fewer than half of participants correctly identified that HCV infection is commonly asymptomatic (46%), that there is currently no vaccine that prevents HCV (19%), and that reinfection after treatment is possible (47%). Very few participants felt that side-effects (9%) or cost of treatment (10%) were barriers to care. Many participants believed that racial disparities exist in the treatment of HCV (59%). The belief that people who use substances are treated inequitably by health care providers was also commonly reported (35% of participants). Self-reported injection drug use and higher HCV-related knowledge were positively associated with previous testing for HCV. Higher HCV-related knowledge was positively associated with HCV antibody positivity at the time of survey completion, though the magnitude of the association was small. Conclusion Interventions are needed to increase knowledge of HCV, to improve access to HCV testing and treatment, and to reduce bias associated with HCV and substance use within the probation population.